Efficiency of fresh milk marketing systems in the Bamako area: some preliminary results - Achuonjei, P.N.; Debrah, S.K. (International Livestock Centre for Africa, 1992)
The marketing systems in sub-Saharan Africa have been alleged to be inefficient, yet relatively little research has been done on marketing efficiency. This study investigates the efficiency of fresh milk marketing in the Bamako area of Mali. A sample of 105 dairy market participants made up of producers, retailers, itinerant milk collectors and wholesalers was interviewed twice a week during the height of the dry and rainy seasons. Fresh milk trade was concentrated in the rainy season when 64 percent of all transactions (by volume) took place. Producers who sold fresh milk directly to consumers handled 45 percent of the total volume compared with 20 percent handled by itinerant collectors. Retail prices observed at the various sale outlets were generally similar after adjusting for transportation costs. On average, traders made a margin of 45 FCFA/litre, which is not excessive relative to services rendered. The preliminary conclusions are that fresh milk marketing in the Bamako area is fairly efficient.